The dynamics of entrepreneurship : evidence from the global entrepreneurship monitor data - Minniti, Maria (Oxford : Oxford University Press, 2011)
At a time when governments all over the world look to entrepreneurship as a way to increase the wealth and well-being of their countries, The Dynamics of Entrepreneurship examines the causes of differences in the levels of entrepreneurship between individuals, the factors that explain variations in the type and quantity of entrepreneurship at aggregate level, and the macroeconomic implications of entrepreneurship. Using the Global Entrepreneurship Monitor (GEM) as a basis for the empirical data, the book brings together contributions from leading scholars to provide a comprehensive overview of current scholarship on entrepreneurial activity.
Includes bibliographical references and index.
oif 17/09/14
Loan
Keywords: Entrepreneurship